2023
DOI: 10.3389/fpls.2023.1127443
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and temporal diversification of the tribe Alsineae (Caryophyllaceae) with the description of three new genera, Hesperostellaria, Reniostellaria and Torreyostellaria

Abstract: Alsineae are one of the most taxonomically difficult tribes in Caryophyllaceae and consist of over 500 species distributed in the northern temperate zone. Recent phylogenetic results have improved our understanding on the evolutionary relationships among Alsineae members. Nevertheless, there are still some unresolved taxonomic and phylogenetic problems at the generic level, and the evolutionary history of major clades within the tribe was unexplored to date. In this study, we carried out phylogenetic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
1
0
0
Order By: Relevance
“…Our divergence time analysis confirmed the results of the previous studies on molecular and temporal diversification of the Caryophyllace family. Analogous to the results of the latest research based on nuclear ITS region and four plastid sequences ( matK , rbcL , rps16 and trnL -F) 118 our studies suggested that the family Caryophyllaceae began to diversify before the end of Crecateous (ca. 74.46 Mya) and this process continued through the Paleogene and Neogene with the highest intensity of the diversification in the last 10 Mya 119 .…”
Section: Discussionsupporting
confidence: 87%
“…Our divergence time analysis confirmed the results of the previous studies on molecular and temporal diversification of the Caryophyllace family. Analogous to the results of the latest research based on nuclear ITS region and four plastid sequences ( matK , rbcL , rps16 and trnL -F) 118 our studies suggested that the family Caryophyllaceae began to diversify before the end of Crecateous (ca. 74.46 Mya) and this process continued through the Paleogene and Neogene with the highest intensity of the diversification in the last 10 Mya 119 .…”
Section: Discussionsupporting
confidence: 87%